(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
In modern conditions, the daily routine of military personnel studying in various educational institutions affects their educational conditions and health status. It is noted in the scientific works of a number of authors, the daily routine of cadets of military higher educational institutions is formed based on their type of education, professional direction and the internal order established in the institution. Imbalances in the cadets’ schedule, if elements of the schedule such as rest, study, nutrition and physical activity are not organized proportionately, can have a negative impact on the origin of various infectious and somatic diseases among the personnel and the educational process of the cadets. A well-organized daily routine is one of the main sources of increasing physical activity of students, enthusiasm for learning and creating and maintaining a healthy environment in the military community.